Explaining Violence In Competitive Sport: Exploring the Root Causes of Violence in Competitive Sport (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This  article seeks to  use   selected sociological theories to  accountfor  the phenomenon  of Violence  in  sport.  Two main theoretical approaches are employed herein: thefunctionalist/structuralist approach and symbolic interactionism. The analysis thatfollows leads to the conclusion that Violence which occurs in sport ispredominantly a consequence of Violence in modern societies. Sport, in turn, isjust a convenient area for violent behaviours to be manifested, which oftenhappens more clearly and conspicuously than in societies